Keabsahan Perkawinan Beda Agama yang Disahkan Pengadilan Negeri Jakarta Pusat Ditinjau dari Undang-Undang Perkawinan dan Hukum Islam - Marsella Auliya Putri; Hendar, Jejen (UNISBA Press, 2024)
Abstract. Interfaith marriages in Indonesia are strictly regulated in the law. Because according to the law, a marriage can be recognized as valid if it is carried out according to the laws of each religion. The basis of religious law in marriage is very important in Law no. 1 of 1974, so the confirmation of marriage depends on religious regulations. This means that in religious law it is said that marriage is not permitted, so it is not permitted by state law, so that whether interfaith marriages are permissible or not depends on the rules of belief. Thus, the legal certainty of interfaith marriages, if they are not carried out according to the laws of each religion, means that the marriage is invalid and unlawful. Basically all religions in Indonesia prohibit interfaith marriages based on Presidential Instruction no. 1 of 1991 KHI article 44 states that mixed marriages between people of different religions, both Muslim men and non-Muslim women, are completely prohibited. Therefore, the legal consequences of interfaith marriages also have an impact on the status and residency of children born, because legitimate children according to Law Article 42 No. 1 of 1974 are children born as a result of a legal marriage. Therefore, the child does not have a civil relationship with his father, but the child has a civil relationship only with the mother and the mother's family. This is regulated in article 43 paragraph 1 of Law no. 1 of 1974 and Article 100 KHI which states that illegitimate children only have a hereditary relationship with their mother and their mother's family. Apart from that, it has legal consequences for the status of population administration. Marriage matters are left more to the laws of each religion that regulates them Abstrak. Perkawinan beda agama di Indonesia secara tegas sudah diatur di dalam Undang- Undang. Karena menurut Undang-Undang suatu perkawinan dapat diakui sah apabila dilangsungkan menurut hukum agama masing-masing. Landasan hukum agama dalam perkawinan sangat penting dalam UU No. 1 tahun 1974, sehingga pengukuhan perkawinan tergantung pada peraturan agama. Artinya dalam hukum agama dikatakan bahwa perkawinan tidak boleh, maka tidak diperbolehkan oleh undang-undang negara, sehingga dalam perkawinan beda agama boleh atau tidaknya bergantung pada kaidah keyakinan. Dengan demikian kepastian hukum perkawinan beda agama jika tidak dilaksanakan menurut hukum masing-masing agama, berarti perkawinan itu tidak sah dan haram hukumnya. Pada dasarnya semua agama di Indonesia melarang pernikahan beda agama berdasarkan Instruksi Presiden No. 1 Tahun 1991 KHI pasal 44 menyatakan bahwa perkawinan campuran yang berbeda agama, baik laki-laki muslim maupun perempuan non-muslim, dilarang sama sekali. Maka dari itu Akibat hukum dari perkawinan beda agama berdampak juga pada status dan kependudukan anak yang dilahirkan, Karena anak yang sah menurut Undang-Undang pasal 42 No 1 Tahun 1974 yaitu adalah anak yang dilahirkan sebagai akibat perkawinan yang sah. Oleh karena itu anak tersebut tidak mempunyai hubungan perdata dengan bapaknya, tetapi anak mempunyai hubungan perdata hanya dengan ibu dan keluarga ibu. Hal ini diatur dalam pasal 43 ayat 1 UU No. 1 Tahun 1974 dan Pasal 100 KHI yang menyatakan bahwa anak di luar nikah hanya mempunyai hubungan turun temurun dengan ibu dan keluarga ibunya. Selain itu, berakibat hukum pada status administasi kependudukan. urusan perkawinan lebih diserahkan kepada hukum masing-masing agama yang mengaturnya.